Science in the Qur'an and its Impact on the Study of Astronomy - Hasibuan, Alya Fathi Muhammad; Hizami Sabil; Abu Yazid Raisal (Universitas Islam Negeri Mataram, 2024)
Science in the Qur'an is a field of study that explores and analyzes Qur'anic verses related to knowledge and natural phenomena. The Qur'an as a holy book in Islam, not only serves as a spiritual guide, but also contains knowledge that is relevant to various aspects of life. There are so many verses of the Qur'an that contain information about the universe, astronomy, geography, biology, physics, and many other Qur'anic verses. The Qur'an gives an overview of the creation of the universe, the laws of nature, and the relationship between man and nature. In addition, the Qur'an also contains information about moral, psychological, and social ethics. The Qur’an is also a guide for humans in creating harmonious relationships in everyday life. The study of science in the Qur'an can provide a deeper understanding of the relationship between religion and science in Islam. This can help in developing a holistic and comprehensive perspective in understanding the universe and the role of humans in it. However, it is important to remember that the interpretation and understanding of Qur'anic verses needs to be done carefully taking into account the historical, linguistic, and cultural context. Science in the Qur'an must be seen as an ever-evolving field of research that requires an objective scientific approach. By studying science in the Qur'an, we can extract valuable and profound information about the universe from life as well as enrich our understanding of the relationship between religion and science